Crossing Rio Pecos - Dearen, Patrick (Book collections on Project MUSE., 2012)
The Pecos River flows snake-like out of New Mexico and across West Texas before striking the Rio Grande. In frontier Texas, the Pecos was more moat than river-a deadly barrier of quicksand, treacherous currents, and impossibly steep banks. Only at its crossings, with legendary names such as Horsehead and Pontoon, could travelers hope to gain passage. Even if the river proved obliging, Indian raiders and outlaws often did not. Long after irrigation and dams rendered the river a polluted trickle, Patrick Dearen went seeking out the crossings and the stories behind them. In Crossin.